Total hip arthroplasty in hip tuberculosis: a systematic review - Shengyuan Zheng; Mufeng Li; Hong Chen; Yanguo Qin (BMC Musculoskeletal Disorders)
Abstract Objectives Tuberculosis of the hip joint is a common form of bone tuberculosis that can cause severe joint destruction and affect quality of life. Total hip arthroplasty (THA) is an important way to treat hip joint-related diseases. In recent years, THA has been applied to treat tuberculosis of the hip joint and has achieved certain results. To this end, we conducted a systematic review of total hip arthroplasty (THA) for the treatment of tuberculosis of the hip. Methods We searched six electronic databases, including the CNKI Database, Wanfang Database, PubMed, Web of Science, Embase, and Cochrane Library, to systematically review and evaluate the literature on hip replacement in patients with acute tuberculative coxitis from the establishment of the database until July 2024. The results of the analysis included patient demographic characteristics, clinical presentation, antituberculosis therapy and surgical protocols, and surgical outcomes. A meta-analysis was performed if the data were available. Results Among a total of 1843 articles, 38 studies were selected, of which 24 studies reported relevant data for meta-analysis. A total of 855 patients (mean age: 34 to 57 years, mean follow-up: 0.5 to 11 years) were enrolled. In general, physicians are accustomed to deciding the appropriate timing of surgery based on inflammatory markers; 90% of the studies recommended preoperative and postoperative antituberculosis therapy (ATT), and 14 studies used antituberculosis drugs during surgery. The majority of the studies used single-stage surgery, and 6 studies used two-stage surgery; cemented prostheses were used in 19.6% of the surgeries, cementless prostheses were used in 79.5% of the surgeries, and hybrid fixation was used in 0.9% of the surgeries. The lateral and posterior approaches were dominant in the included studies. In all the studies, 34 patients experienced disease reactivation. The average complication(defective healing, followed by aseptic loosening, dislocation, deep venous thrombosis, and so on) rate was 11.2%(39/300 cases). The mean Harris hip score (HHS) at the final follow-up was 89.05. Conclusion THA is an effective method for treating tubercular arthritis of the hip. In the past, it was thought to increase the risk of disease reactivation, but studies have shown generally favorable results, THA could significantly improve patients’ quality of life. Two-stage surgery can be used in complex patients at greater risk. A long course of multidrug antituberculosis therapy is crucial for preventing reactivation and enhancing the effectiveness of surgery.